A concise overview on pesticide detection and degradation strategies. Issue 1 (31st December 2022) - Sur, Saheli; Sathiavelu, Mythili
ABSTRACT: Pesticides are a gift to agriculture for its flourish of crop production. For production of heavy grown crops, growing multiple crops in a season or enriching the soils for better productivity, pesticides are a mandate in modern world to meet the food requirement. However, controversy arises on the fact of overuse and the underlying problems associated with it. The problems include environmental contamination, public health compromisation, disturbance in the ecological niches, long-term persistence in soil and water bodies, etc. Pesticide residues present in the foods or crops may get circulated by bioamplification through the food chains. Therefore, it is imperative to detect the pesticides present in the environment and decontaminate the same by degradation to maintain the safety of environment. This review outlines the recent strategies of various pesticide detection techniques and discusses the overview of degradation strategies worked on for removal of pesticides from the environment.Pesticides are a gift to agriculture for its flourish of crop production. For production of heavy grown crops, growing multiple crops in a season or enriching the soils for better productivity, pesticides are a mandate in modern world to meet the food requirement. However, controversy arises on the fact of overuse and the underlying problems associated with it. The problems include environmental contamination, public health compromisation, disturbance in the ecological niches, long-term persistence in soil and water bodies, etc. Pesticide residues present in the foods or crops may get circulated by bioamplification through the food chains. Therefore, it is imperative to detect the pesticides present in the environment and decontaminate the same by degradation to maintain the safety of environment. This review outlines the recent strategies of various pesticide detection techniques and discusses the overview of degradation strategies worked on for removal of pesticides from the environment.